1991
DOI: 10.1002/bsl.2370090303
|View full text |Cite
|
Sign up to set email alerts
|

Recent research on the relationship between illicit drug use and crime

Abstract: This article reviews research on the relationship between illicit drug use and crime conducted since 1980. Significant advances are noted in studies of the crime of known drug abusers and in studies of the drug use of individuals processed by the criminal justice system. Major conclusions supported by the results of studies of the criminal activity of narcotic abusers are that both a higher prevalence and higher rates of crime are associated with more frequent use of heroin and/or cocaine, although addicts var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 58 publications
1
58
0
3
Order By: Relevance
“…Violence occurs in this instance due to unanticipated circumstances such as the presence of a weapon or the reaction of the victim (Goldstein et al, 1989). Drugs most associated with economic-compulsive violence are heroin and cocaine due to their compulsive pattern of use and financial cost (Goldstein, 1985;Hunt, 1991;Nurco et al, 1991). Other environmental factors that have been found to be correlated with substance use and violence include lower education, unemployment, a history of imprisonment, as well as a higher number of psychiatric diagnoses.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Violence occurs in this instance due to unanticipated circumstances such as the presence of a weapon or the reaction of the victim (Goldstein et al, 1989). Drugs most associated with economic-compulsive violence are heroin and cocaine due to their compulsive pattern of use and financial cost (Goldstein, 1985;Hunt, 1991;Nurco et al, 1991). Other environmental factors that have been found to be correlated with substance use and violence include lower education, unemployment, a history of imprisonment, as well as a higher number of psychiatric diagnoses.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Longitudinal studies have consistently found that rapid relapse to opioid (principally, heroin) addiction following incarceration is a continuing problem. Several reports indicate that readdiction is typically well established within 90 days of release (Office of National Drug Control Policy, 1999;Stewart, 1995;Wexler, Lipton, & Johnson;1988), whereas other reports have found that most incarceration episodes are followed by relapse as early as 1 month after release (Kinlock, Battjes, & Schwartz, 2002; Maddux & Desmond, 1981;Nurco, Hanlon, & Kinlock, 1991).…”
Section: Abstract Heroin Addiction; Prisoners; Methadone Maintenancementioning
confidence: 99%
“…Longitudinal studies have consistently found that rapid relapse to opioid (principally, heroin) addiction following incarceration is a continuing problem. Several reports indicate that readdiction is typically well established within 90 days of release (Office of National Drug Control Policy, 1999;Stewart, 1995;Wexler, Lipton, & Johnson;1988), whereas other reports have found that most incarceration episodes are followed by relapse as early as 1 month after release (Kinlock, Battjes, & Schwartz, 2002; Maddux & Desmond, 1981;Nurco, Hanlon, & Kinlock, 1991).In addition to its high prevalence, readdiction to heroin is accompanied by increased criminal activity (Chaiken & Chaiken, 1990;Kinlock, O'Grady, & Hanlon, 2003;Nurco, 1998), disproportionately high risk of HIV infection (Chitwood, Comerford, & Weatherby, 1998; Correspondence concerning this article should be addressed to Timothy W. Kinlock Inciardi, McBride, & Surratt, 1998), Hepatitis B and C infections (Edlin, 2002;Fuller, Vlahov, Safeian, Ompad, & Strathdee, 1999;Hagan et al, 2002) (Inciardi et al, 1998;Mark et al, 2001), and impaired parenting (Keller, Catalano, Haggerty, & Fleming, 2002). Thus, the development and implementation of effective drug abuse treatment strategies for incarcerated offenders with heroin-addiction histories is urgently needed, not only for such individuals' rehabilitation but also for their survival and for the safety and welfare of the public (Kinlock et al, 2002;Rich, Boutwell, et al, 2005; SmithRohrberg, Bruce, & Altice, 2004).…”
mentioning
confidence: 99%
“…D'abord, on trouve le modèle psychopharmacologique selon lequel les SPA induisent des comportements violents chez les individus intoxiqués (Goldstein, 1985). Aussi, le modèle économico-compulsif est présent dans le discours (Nurco et al, 1991). Celui-ci explique la délinquance lucrative chez les personnes alcooliques ou toxicomanes par le fait qu'elles ne peuvent pas assumer financièrement les dépenses qu'occasionne leur dépendance.…”
Section: Conséquences De L'usage Abusif De Spaunclassified